Analisis Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Puskesmas Taman Mataru Di Desa Taman Mataru Kecamatan Mataru Kabupaten Alor - Anita Maria Malaikari (Jurnal Ilmiah Wahana Pendidikan, 2023)
Anita M. Malaikari (2023). Thesis Title Analysis of the Effect of Service Quality Dimensions on Patient Satisfaction at Taman Mataru Health Center, Mataru District Alor Regency. Advisor I : Ferdinand R. Anigomang, SE., MM and Supervisor II : Junius M. Sau Sabu, SE., MAkt. This study aims to determine the effect of service quality on patient satisfaction at Taman Mataru Health Center, Mataru District, Alor Regency. This type of research is quantitative research with data collection techniques namely observation, interviews, and documentation studies. This study uses primary data, population and sample is patient satisfaction at Taman Mataru Health Center, Mataru District, Alor Regency. There were 35 patients and the sampling technique in this study was random sampling or saturated samples because the population was under one hundred N = n. Then the entire population is used as a sample in this study. The statistical method used in this research is multiple linear regression by looking at the significant value of the t test and the significant value of the F test as a benchmark in taking the hypothesis. The results of this study indicate that, partially the reliability variable has a significance value of 0.016 or 1.6% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which says that the reliability variable partially has a positive effect on Patient Satisfaction at Taman Mataru Health Center, Mataru District, Alor Regency. Partially the responsiveness variable has a significant value of 0.036 or 3.6 where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the responsiveness variable partially has a positive effect on patient satisfaction at the Puskesmas Mataru Park, Mataru District, Alor Regency. Partially the guarantee variable has a significant value of 0.026 or 2.6 where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the guarantee variable partially has a positive effect on patient satisfaction at Taman Mataru Health Center Mataru District, Alor Regency. Partially the direct evidence variable has a significant value of 0.028 or 2.8 where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H4 which states that the direct evidence variable partially has a positive effect on patient satisfaction at the health center Mataru Park, Mataru District, Alor Regency. Partially the empathy variable has a significant value of 0.000 or 0.0 where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H5 which states that the empathy variable partially has a positive effect on patient satisfaction at Taman Mataru Health Center Mataru District, Alor Regency.